Secularization - Turner, Charles, 1962- (Abingdon, Oxon ; New York, NY : Routledge, 2019)
"'Secularization' sounds simple, a decline in the power of religion. Yet, the history of the term is controversial and multi-faceted; it has been useful to both religious believers and non-believers and has been deployed by scholars to make sense of a variety of aspects of cultural and social change. This book will introduce the reader to this variety and show how secularization bears on the contemporary politics of religion. Secularization addresses the sociological classics' ambivalent accounts of the future of religion, later and more robust sociological claims about religious decline, and the most influential philosophical secularization thesis, which says that the dominant ideas of modern thought are in fact religious ones in a secularized form. The book outlines some shortcomings of these accounts in the light of historical inquiry and comparative sociology; examines claims that some religions are 'resistant to secularization'; and analyses controversies in the politics of religion, in particular over the relationship between Christianity and Islam and over the implicitly religious character of some modern political movements. By giving equal attention to both sociological and philosophical accounts of secularization, and equal weight to ideas, institutions and practices, this book introduces complicated ideas in a digestible format. It will appeal to students and scholars interested in making unusual connections within sociology, anthropology, philosophy, theology and political theory"--
Influence: is that all there is?Smaller narratives and secularization struggles; War; Instead of secularization, the creation of secular spaces: Israel; Note; 6. Fundamentalism, zombie religion, secular religion; The revenge of God; Political and religious controversy as alaboratory; Secular religion?; 7. An inconclusive conclusion; Bibliography; Index
OCLC-licensed vendor bibliographic record.
Keywords: Secularization; Secularism; SOCIAL SCIENCE / General; SOCIAL SCIENCE / Sociology / General